Using anion recognition to control the folding and unfolding of a single chain phosphorescent polymer. Issue 62 (21st July 2017) - Ji, Xiaofan; Guo, Chenxing; Ke, Xian-Sheng; Chi, Xiaodong; Sessler, Jonathan L.
Abstract : Calix[4]pyrrole-based anion recognition allows control over the folding and unfolding of a single PMMA polymeric chain bearing pendant calix[4]pyrrole and Pt(ii ) porphyrin subunits. Abstract : We report here the use of anion recognition to control the folding and unfolding of a single polymeric chain consisting of a PMMA bearing pendant calix[4]pyrrole and Pt(ii ) porphyrin subunits.